2007
DOI: 10.1002/arch.20224
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoic acid O‐methyl transferase (FAMeT) isoforms: Conserved traits and gene expression patterns related to caste differentiation in the stingless bee, Melipona scutellaris

Abstract: Farnesoic acid O-methyl transferase (FAMeT) is the enzyme that catalyzes the formation of methyl farnesoate (MF) from farnesoic acid (FA) in the biosynthetic pathway of juvenile hormone (JH). This work reports the cloning, sequencing, and expression of FAMeT gene from the stingless bee Melipona scutellaris (MsFAMeT). The MsFAMeT in silico analysis showed that greatest sequence similarity is found in Apis mellifera and other insects, while relatively less similarity is shown in crustaceans. Evidence of alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…In this study, the production of MF was shown to increase in relation to increasing amounts of recombinant FAMeT in a radiochemical assay (Gunawardene et al, 2002). However, subsequent studies in other Crustacea (Litopenaeus vannamei, Homarus americanus, Cancer pagurus) and insect species (Ceratitis capitata, Nilaparvata lugens and Melipona scutellaris) did not verify this activity (Holford et al, 2004;Hui et al, 2008;Liu et al, 2010;Ruddell et al, 2003;Vannini et al, 2010;Vieira et al, 2008). Moreover, two recent studies in D. melanogaster have shown that DmFAMeT is not involved in JH biosynthesis (Burtenshaw et al, 2008;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 46%
“…In this study, the production of MF was shown to increase in relation to increasing amounts of recombinant FAMeT in a radiochemical assay (Gunawardene et al, 2002). However, subsequent studies in other Crustacea (Litopenaeus vannamei, Homarus americanus, Cancer pagurus) and insect species (Ceratitis capitata, Nilaparvata lugens and Melipona scutellaris) did not verify this activity (Holford et al, 2004;Hui et al, 2008;Liu et al, 2010;Ruddell et al, 2003;Vannini et al, 2010;Vieira et al, 2008). Moreover, two recent studies in D. melanogaster have shown that DmFAMeT is not involved in JH biosynthesis (Burtenshaw et al, 2008;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 46%
“…Since the FAMeT gene seems to be fairly conserved among insects, gene identification based only on its nucleotide or deduced amino acid sequence is difficult. A domains and motif analysis is therefore necessary, as suggested for the M. scutellaris FAMeT (Vieira et al, 2008). As reported for M. scutellaris FAMeT, the Ceratitis sequence shows three CK2 phosphorylation sites, suggesting a similar biosynthetic pathway for both genes.…”
Section: Discussionmentioning
confidence: 90%
“…: AM493718 and AM493719) described by Vieira et al (2008). As observed for the Ceratitis sequence, the isoform 1 shows two DM9 domains (GenBank accession no.…”
Section: Analysis Of Putative-famet Deduced Proteinmentioning
confidence: 82%
See 1 more Smart Citation
“…Some reports identified specific functional genes involved in caste development (Corona et al, 1999;Yamazaki et al, 2006;Lattorff et al, 2007;Aamodt 2008;de Azevedo et al, 2008). Others screened clusters of genes that belonged to distinctly different evolutionary and functional groups and pathways (Evans et al, 1999;Patel et al, 2007;Vieira et al, 2008). In this study, differential feeding of female larvae promotes the occurrence of two different phenotypes from identical genotypes.…”
Section: Discussionmentioning
confidence: 78%